Strengthening Early Childhood Character Education - Rahmi, Elvi; Felayati, Felayati; Ningsih, Setia Yulis; Efendi, Efendi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
Morality is a problem that will never stop being studied and explored. In the world of education, it is very necessary to have good morals and character. If from an early age children are taught to have good character and manners and be independent, then eventually they will be more accustomed to it as adults. By conducting a study at PAUD Sungai Sapih Peduli, God willing, a strong generation with good and noble character will be created. This type of research uses natural qualitative research, namely using the habit method which takes place at PAUD Sungai Sapih Peduli. The data sources used in this study are primary and secondary data sources. The data collection methods used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and verification. And to test the validity of the data using triangulation of sources and techniques. Based on the results of research and data analysis, it can be concluded that: 1) The description of character education in strengthening character education in Sungai Sapih Peduli Early Childhood Education is implemented through exemplary methods and habituation methods that are carried out continuously and sustainably by applying character education values ​​including: behavior, patience, politeness, discipline, independence, and having an attitude of tolerance/social care. 2) The factors that influence character education in strengthening character education are divided into two, namely supporting factors and inhibiting factors. Supporting factors are, the school environment through good behavior and examples from the principal, and teachers, teacher readiness in conducting learning in accordance with SOPs and the use of methods used.